Plasma adrenomedullin levels in asthmatic patients - KARAKURT, SAİT (My University, 2001)
Adrenomedullin (ADM) is a newly discovered endogenous vasorelaxing peptide isolated from pheochromocytoma. Some experimental studies suggest that ADM plays a role in asthma. The purposes of the present study were to assess the plasma ADM levels in adults with mild to severe asthma and controls and to correlate those with the findings on lung function test results and other clinical indices. We recruited 16 mild, 10 moderate, and 11 severely asthmatic patients and 12 healthy controls. We measured the plasma concentrations of ADM in patients with asthma and in healthy subjects using RIA. We assessed FEV1, FEV1 predicted %, FEV1/FVC, symptom score, IgE, ECP, and morning and evening peak expiratory flow measurements. There was no significant difference between the asthmatic and the control group ADM levels, which were 26.3 +/- 24.2 pg/mL and 22.9 +/- 17.6 pg/mL, respectively. Furthermore, plasma ADM levels increased as the severity of the disease increased in asthmatic patients (20.7 +/- 14.4 pg/mL in mild, 25.2 +/- 24.3 pg/mL in moderate, and 35.5 +/- 33.6 pg/mL in severe asthmatics), although they did not result in any statistical significance. However, the plasma ADM levels correlated negatively with the FEV1 levels in the asthmatic group (p < 0.02, r = -0.37). Peripheral blood eosinophilia, IgE, and ECP levels did not correlate with plasma ADM levels. These results suggest that the measurement of ADM concentration in plasma will not be of diagnostic use in asthma, but may be a reflection of the severity of asthma.
Keywords: Adult; Female; Humans; Middle Aged; Male; Case-Control Studies; Vasodilator Agents; Peptides; Asthma; Respiratory Function Tests; Immunoglobulin E; Skin Tests; Adrenomedullin; Eosinophilia; Calcitonin Gene-Related Peptide